The Role of Founders' Entrepreneurial Mindset in Shaping the Journey of Digital Startups - Junaedi, I Wayan Ruspendi; Waruwu, Dermawan (American Journal of Business Science Philosophy, 2024)
This study investigates the critical role of entrepreneurship in driving the growth and success of digital startups, highlighting its significance in fostering innovation, technological advancement, and economic transformation. Using a qualitative approach, semi-structured interviews were conducted with ten digital startup founders to explore the opportunities, challenges, and strategies shaping their ventures. The findings reveal that entrepreneurship enables startups to leverage technological advancements, access global markets, and optimize operational costs through digital tools, scalable platforms, and partnerships with accelerators and venture capitalists. Despite these opportunities, digital startups face significant challenges, including limited funding access, intense competition, and regulatory compliance issues. The research identifies effective strategies such as adopting agile methodologies, building robust networks, fostering innovation, and emphasizing leadership, team-building, and customer-centric approaches as critical to sustaining growth and achieving long-term success. By addressing gaps in existing literature that often focus on technological and operational factors, this study underscores the strategic importance of entrepreneurship in navigating the complexities of the digital business landscape. The implications extend beyond academic discourse, providing actionable insights for entrepreneurs to refine their approaches, policymakers to create enabling regulatory environments, and ecosystem stakeholders to support innovation. These findings contribute to a deeper understanding of entrepreneurship’s transformative potential and its role in empowering digital startups to thrive in a dynamic and competitive global economy.
Keywords: entrepreneurship; startups; innovation; startup ecosystem; strategic leadership